2017
DOI: 10.3892/etm.2017.4280
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rb3 strengthens the hypoglycemic effect through AMPK for inhibition of hepatic gluconeogenesis

Abstract: Abstract. Ginsenoside Rb3 is one of the major active components in protopanaxdiol type ginsenosides, and has demonstrated anti-diabetic activity. However, the mechanism of this action has yet to be elucidated. The present study investigated the effects of ginsenoside Rb3 on the AMP-activated protein kinase (AMPK) gluconeogenesis pathway. The present study involved the use of HepG2 cells and western blot analysis to systematically evaluate the effect of ginsenoside Rb3 on AMPK signaling proteins and key factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 24 publications
0
14
2
Order By: Relevance
“…The mechanisms underlying the modulation of glucose metabolism by RGE in patients with DM would likely be perturbation of hepatic glucose production and enhancement of glucose uptake through glucose transporter 4 (GLUT4) into peripheral tissues. Recently, ginsenosides Rb1, Rb2, Rg1, Rg3, Rh2, and compound K, major pharmacological components of RGE, have been reported to suppress the hepatic gluconeogenesis via adenosine monophosphate (AMP)-activated protein kinase (AMPK) [ 22 , 23 , 24 ]. Importantly, enhanced GLUT4 expression mediated by activated insulin receptor substrate (IRS)/phosphatidylinositol-3,4,5-triphosphate (PI3K)/serine-threonine protein kinase signaling pathway by the treatment of RGE or ginsenosides increased glucose uptake in adipocytes or skeletal muscle cells and, thereby, decreased blood glucose or Hb-A1c levels [ 22 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms underlying the modulation of glucose metabolism by RGE in patients with DM would likely be perturbation of hepatic glucose production and enhancement of glucose uptake through glucose transporter 4 (GLUT4) into peripheral tissues. Recently, ginsenosides Rb1, Rb2, Rg1, Rg3, Rh2, and compound K, major pharmacological components of RGE, have been reported to suppress the hepatic gluconeogenesis via adenosine monophosphate (AMP)-activated protein kinase (AMPK) [ 22 , 23 , 24 ]. Importantly, enhanced GLUT4 expression mediated by activated insulin receptor substrate (IRS)/phosphatidylinositol-3,4,5-triphosphate (PI3K)/serine-threonine protein kinase signaling pathway by the treatment of RGE or ginsenosides increased glucose uptake in adipocytes or skeletal muscle cells and, thereby, decreased blood glucose or Hb-A1c levels [ 22 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some ginsenosides exert blood glucose lowering effects in this way. Researches confirmed that ginsenoside Rg1 (Liu et al, 2017 ), Rb3 (Meng et al, 2017 ) and, compound K (Wei et al, 2015 ) reduced gluconeogenesis through increased AMPK expression and decreased FOXO1 activity, which may offer a potential treatment for type 2 diabetes. Ginsenoside Rg5 prevented gluconeogenesis via the suppressing of HIF-1α (Xiao et al, 2017 ) expression.…”
Section: Reducing Gluconeogenesismentioning
confidence: 90%
“…MTT assays were conducted to monitor cell viability ( 27 , 28 ) as follows: C2C12 myotubes treated for 24 to 48 h with various concentrations of DEX (0, 25, 50, 100 or 200 µM) ( 29 ) or with S-Rg3 (0, 0.02, 0.2 or 2 µM) and/or DEX (200 µM) for 24 h were incubated with MTT (0.5 mg/ml) for 4 h. All treatments were conducted at 37°C. Next, formazan dissolved in 150 µl DMSO was added to wells then measurements of absorbance levels of wells were taken at a wavelength of 490 nm at room temperature.…”
Section: Methodsmentioning
confidence: 99%